What Gets Measured Gets Done: Calculating the Value of Professional Service - Fabry, Dave (Seminars in Hearing, 2019)
In many practices, the role of professional service in the hearing aid delivery process has been obfuscated by the use of bundled pricing models. Emerging direct-to-consumer and third-party administrator hearing aid distribution channels will further challenge practitioners to examine how, and if, they choose to participate with new strategies to increase hearing aid adoption rates. This article focuses on providing a straightforward method for calculating revenue per clinical hour required to maintain quality, professionally driven, and profitable care in the hearing aid diagnostic, selection, fitting, and follow-up process. Furthermore, by measuring the value of clinical service, it uncouples the professional from the technology, and provides a tool for assessing how they can improve clinical efficiencies without compromising best practice or clinical outcomes.
Keywords: audiology; hearing aids; revenue per hour; gross margin per hour; private practice